2002
DOI: 10.1007/s00464-001-9181-8
|View full text |Cite
|
Sign up to set email alerts
|

A new method of preemptive analgesia in laparoscopic cholecystectomy

Abstract: Our results support the clinical validity of preemptive analgesia, but the timing of intraperitoneal administration of local anesthetic is very important. Only application before creation of the pneumoperitoneum may preempt every neuronal central sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 24 publications
1
74
0
7
Order By: Relevance
“…These results are comparable with studies conducted by Berczynski et al and Maestroni et al Maestroni et al also observed that pain was significantly less in patients who received ropivacaine as compared to saline before creation of pneumoperitoneum. 8,9 However, Lee et al concluded that no significant difference in abdominal pain occurred by preemptive instillation of Bupivacaine in laparoscopic cholecystectomy. 10 This lack of effect in their study might be due to small dosage of intraperitoneal Bupivacaine used (0.25% 40 ml) as compared to our study in which we used 0.5% Ropivacaine 3mg/kg The traditional approach to postoperative analgesia is to start therapy when surgery is completed and pain is experienced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are comparable with studies conducted by Berczynski et al and Maestroni et al Maestroni et al also observed that pain was significantly less in patients who received ropivacaine as compared to saline before creation of pneumoperitoneum. 8,9 However, Lee et al concluded that no significant difference in abdominal pain occurred by preemptive instillation of Bupivacaine in laparoscopic cholecystectomy. 10 This lack of effect in their study might be due to small dosage of intraperitoneal Bupivacaine used (0.25% 40 ml) as compared to our study in which we used 0.5% Ropivacaine 3mg/kg The traditional approach to postoperative analgesia is to start therapy when surgery is completed and pain is experienced.…”
Section: Resultsmentioning
confidence: 99%
“…Maestroni et al also observed a significantly lower total pain intensity and total analgesic requirement during initial 8 hrs postoperatively. 9 But Lee et al have concluded that intraperitoneal bupivacaine had no significant effect on duration of first analgesic requirement and total analgesic requirements. 10 Alper I et al also studied the effects of intraperitoneal administration of levobupivacaine on pain after LC by intraperitoneal instillation of either 40 mL of 0.25% levobupivacaine in study group or normal saline in control group under direct vision into the hepatodiaphragmatic lodge and above the gallbladder after creation of pneumoperitoneum.…”
mentioning
confidence: 99%
“…Levobupivacaine given to the subdiaphragmatic region may block the nociceptive stimuli of diaphragmatic peritoneum. In the previous studies, intraperitoneal local anaesthetic application was found to be effective in reducing shoulder pain (12,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that pain in the shoulder is the result of diaphragmatic stretching resulting in phrenic nerve neuropraxia (31). In order to reduce this, lower insufflation pressure and careful decompression may be the key to lowering pain.…”
Section: Discussionmentioning
confidence: 99%
“…Some trials have preemptively used dextromethorphan {an NMDA (N-methyl-D-aspartate) receptor antagonist}, NSAIDS, opiods, epidural, and multimodal analgesia with positive results in reducing pain among patients (4,36,37). Other trials assessing the role of local anaesthetic given preemptively in the form of intraperitoneal instillation were also conducted where local anaesthetic agent were given intraperitoneally and compared with placebo or groups with instillation at the end of operation (31,(38)(39)(40). However, these techniques can only be conducted after extensive literature review and large-scale multi-centre trials since evidence of the use of these modalities does not appear to be supported by large number of evidence-based literatures (4,17).…”
Section: Discussionmentioning
confidence: 99%